Errors in controlling cars cause tragic accidents involving motorcyclists - Wrona Rafał (De Gruyter, 2021)
The article deals with the issue of road safety and the threats caused by unexpected maneuvers of passenger cars pulling into the opposite lane, directly in front of an oncoming two-wheeler. The first part discusses the legal regulations that apply to vehicle drivers. In the second part, road accidents are presented, while in the next part, examples of road accidents are analyzed in terms of their causes. The article deals with the causes of road accidents. The tragic consequences of the analyzed accidents require this problem to be addressed in research. This is especially true of the question of why car drivers usually notice only an oncoming car and not a two-wheeled vehicle?